2006
DOI: 10.1016/j.jcis.2006.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of complexed species of Eu in alumina-bound and free polyacrylic acid: A spectroscopic study

Abstract: The speciation of Eu complexed with polyacrylic acid (PAA) and alumina-bound PAA (PAA ads ) was studied at pH=5 in 0.1M NaClO 4 . Structural parameters were obtained from 7 coordination. The results show that the degree of freedom of carboxylate groups is not the same for free or adsorbed PAA. For PAA, the degree of freedom is constrained by the flexibility of the methylene chain. When PAA is adsorbed on alumina, the polymer chains cannot any more be treated as independent chains. One may rather assume format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
4
13
0
Order By: Relevance
“…A similar species is therefore expected in EuPAA and EuPAA ads complexes. All these conclusions are in agreement with those reported in a previous study performed with Eu as a function of r by laser-induced fluorescence spectroscopy using 7 F 0 → 5 D 0 excitation spectra [16].…”
Section: Effect Of Metal Ion Loadingsupporting
confidence: 93%
See 1 more Smart Citation
“…A similar species is therefore expected in EuPAA and EuPAA ads complexes. All these conclusions are in agreement with those reported in a previous study performed with Eu as a function of r by laser-induced fluorescence spectroscopy using 7 F 0 → 5 D 0 excitation spectra [16].…”
Section: Effect Of Metal Ion Loadingsupporting
confidence: 93%
“…Data are already available for Eu [16]. In this study, the previous data were completed with Cm, which has the advantage of being more sensitive than Eu.…”
Section: With [M] P Being the Concentration Of Complexed M Andmentioning
confidence: 99%
“…Fan et al [28] studied Eu(III) sorption onto attapulgite in different KNO 3 solutions, and found that the sorption was dependent on ionic strength at pH \5.5 and independent of pH at pH[5.5. Similar sorption behavior were also found for Eu(III) interaction with other kinds of materials such as carbon nanotube/iron oxide magnetic composites [33], graphene oxides [34,35], montmorillonite [36] and alumina oxides [37][38][39][40][41].…”
Section: Effect Of Ionic Strength and Phsupporting
confidence: 74%
“…An illustration of both coordination modes is given in figure S3, for the case of the Yb-actetate complex. Indeed, lanthanides or actinides\O bond distances in the case of COO bi are generally longer than for COO mono as shown for Eu-polyacrylic acid (Montavon et al, 2006) or as discussed for U(VI) (Schmeide et al, 2003;and references therein). This is particularly well illustrated in the structure of Yb-formate determined by XRD (Furmanova et al, 1983), where formate coordinated to Yb in both modes.…”
Section: Exafs Analysis Of the Reference Yb-ligand Complexesmentioning
confidence: 77%